PERKAWINAN ONLINE MASA PANDEMI COVID-19 - Nyimas Shafa Amira Berliana (2021)
Up until now, online marriage has not received legal protection in Indonesia. This study aims to analyze the practice of online marriage and its legal implications in the marriage law system in Indonesia. This study is important to fill the gap of legal law since online marriage has not received legal protection in Indonesia. This research is a qualitative research using normative empirical approach. Sources of data used in this study include the Al-Qur'an, Hadith, Jurisprudence on Marriage, Law Number 1 of 1974 concerning Marriage, Compilation of Islamic Law (KHI), and Fatwas and opinions of Indonesian scholars. With data collection techniques using literature study and digital ethnography. This study shows that online marriages occur during the Covid-19 pandemic are legal as long as they meet the conditions and the principle of marriage. Even though there are differences of opinion between the scholars, the Al-Qur'an and Hadith they are strongly recommend the occurrence of marriage, since marriage is better carried out to avoid adultery. Therefore, it is necessary to have regulations regarding online marriage so that it can be a definite solution to carry out marriage in the midst of the Covid-19 pandemic.